The Development of Student Worksheet to Support ICARE Learning Model on Optical Equipment Material - Abdul Hamid; Ngadimin Ngadimin; Nani Azwi (Asian Journal of Science Education, 2020)
ABSTRACTThis research aimed to determine the feasibility of the development of student worksheets to support ICARE learning model on optical material in MAS Darul Ihsan Aceh Besar. Student worksheets developed based on the elements found in the ICARE learning model. The type of research was Research and Development (RD) and the development design used in this research was ADDIE namely Analysis, Design, Development, Implementation and Evaluation. Student worksheets assessed by the validation team obtained a percentage of 84.2% with excellent category, then the students’ responses gained a percentage of 82.5% with excellent category. Therefore, students’ worksheets to support ICARE learning model on optical material was appropriate to be implemented in learning process. Keywords: Student worksheets, ICARE learning Model